Laser-Induced Magnetization Dynamics in Si-Doped Yttrium-Iron Garnet Film - Mikhail Gaponov; Sergey Ovcharenko; Nikita Ilyin; Elena Mishina (Condensed Matter, 2022)
We experimentally demonstrate that the excitation of a silicon-doped yttrium-iron garnet film by femtosecond laser pulses triggers a magnetization precession with an amplitude determined by the external magnetization direction. The maximum efficiency is achieved at the pump wavelength corresponding to the absorption maximum due to doping with silicon ions. Based on the azimuthal dependences of the precession amplitude and frequency, it is shown that the magnetization dynamics is induced by a thermal disruption of the magnetocrystalline anisotropy. By modeling hysteresis loops, it was found that the silicon doping leads to a decrease in the value of the exchange interaction in the film and an increase in the anisotropy field.